Diversity of Antioxidant Content and Its Relationship to Grain Color and Morphological Characteristics in Winter Wheat Grains - Dong-yun MA; De-xiang SUN; Yi ZUO; Chen-yang WANG; Yun-ji ZHU; Tian-cai GUO (Journal of Integrative Agriculture, 2014)
The current interest in the health benefits of whole wheat grain has prompted breeders to further increase the concentration of antioxidants in wheat. The objective of this study was to investigate the variation in antioxidant content among Chinese wheat grains and the relationship between antioxidants and grain color and morphological characteristics. A wide variation was observed in the total phenolic, carotenoid and flavonoid contents, as well as the antioxidant activity (AOA), of Chinese wheat varieties. Black wheat had the highest mean total phenolic, carotenoid and flavonoid contents and the highest AOA, followed by red and white wheats. The grain color parameters were significantly negatively correlated with total phenolic, carotenoid and flavonoid contents and AOA among all of the wheat varieties examined, and grain weight was also significantly negatively correlated with these traits. The same correlation between grain weight and antioxidant traits was also observed within individual groups of wheat, which indicates that grain weight may be used as an index for selecting wheat varieties with high AOA. Landraces had significantly higher flavonoid content than commercial wheat varieties. The results of this study may be useful for breeding nutrient-rich wheat varieties.